O ensino das Leis de Kepler com a mediação por histórias em quadrinhos - Júnior, Luiz Cláudio Chiavini Oliveira (2023)
C. O. Junior, Luiz Cláudio. The Teaching of Kepler's Laws Mediated by Comics. 2023. Dissertation (Master in Physics Teaching) – Federal University of São Carlos, Sorocaba campus, Sorocaba, 2023. The motivation for this work was born out of the COVID-19 pandemic situation in 2020, where many students were unmotivated to attend remote classes. The idea arose to create attractive material with accessible language that could be used by students in a remote context. The Physics content addressed was chosen according to the content of the academic year, where we opted for the discussion of Kepler's three laws. The choice for the development of comics’ book came from the interest that usually exists in relation to this style of text. As a theoretical framework for teaching-learning, Lev Vigotsky's ideas were used, considering the concepts of mediator, which would be the comics, and zone of proximal development. The educational product consisted of 3 comics, each one addressing a Kepler's Law and an evaluative activity elaborated in the same language as the comics. The elaboration of this product was divided into several stages from the development of the material, following the necessary steps in the idealization and production of a comic book, passing through an application test with the research group, exposition of the content in the classroom using the digital tool Nearpod and finally the application of the evaluative activity. According to the students' reports, the use of comics has great potential to assist in their studies.